Analisis Usahatani Tanaman Bawang Merah (Allium Ascalonicum L) di Kebun Praktek Fakultas Teknologi Pangan, Pertanian dan Perikanan Universitas Nusa Nipa - Yohanes Melkior; Fiator Nong; Gabriel Otan Apelabi (Peneliti.net, 2023)
Horticultural commodities have an important role in Indonesian agriculture, considering that these commodities are potential commodities that have high economic value that can continue to be developed. Shallot farming has a fairly open market potential because the demand and demand for shallots continues to increase every year. The purpose of the study was to determine the analysis of income level and feasibility of shallot farming in the Practice Garden of the Faculty of Food Technology, Agriculture and Fisheries, Nusa Nipa University of Indonesia. The population in this study was all employees in the practice garden with a total of 7 people and sampling was carried out by census which took 1 person, namely the head of the practice garden to be the respondent. The data collection techniques used are interviews and questionnaires. The results of the study found that the total cost of onion farming with a land area of 5,000 m2 was Rp. 38,490,000.00 where the total revenue obtained was Rp. 64,000,000.00 and the total income from the farming business run was Rp. 25,510,000.00. The value of the R / C Ratio obtained from onion farming activities is 1.66 so that with an R / C Ratio value greater than 1, the farming business is feasible to run.